DESIGN OF DECISION SUPPORT SYSTEM DAMAGE DIAGNOSIS OF HONDA BEAT MOTORCYCLE MATIC USING FORWARD CHAINING METHOD - Sugiarto Sugiarto; Rohmad Haryadi (Badan Penerbit STIEPARI Press, 2022)
An expert system is a system that seeks to adopt human knowledge to a computer that is designed to model problem solving abilities like an expert (Durkin, 1994). The three main components contained in any expert system are the knowledge base, the inference engine, and the user interface. Forward chaining is a strategy to predict or find a solution to a problem that starts with a set of known facts, then derives new facts based on rules whose premises match the known facts. This process is continued until the goal is reached or there are no more rules whose premise matches the known facts. The system maker application media uses PHP and MySQL as databases